A New Appraisal of Lithospheric Structures of the Cordillera‐Craton Boundary Region in Western Canada. Issue 9 (22nd September 2018) - Chen, Yunfeng; Gu, Yu Jeffrey; Hung, Shu‐Huei
Abstract: The Western Canada Sedimentary Basin marks a boundary zone between the Precambrian North American craton and the Phanerozoic Cordillera. Its crystalline basement has documented more than 3 billion years of evolution history of western Laurentia. Here we conduct a high‐resolution survey of the mantle P and S wave velocities using finite‐frequency tomography. Our models show pronounced eastward increases of 4% P and 6% S wave velocities beneath the foreland region, which define a sharp seismic Cordillera‐Craton boundary. In the cratonic region, distinctive high‐ (>2%) velocity anomalies representing depleted mantle lithospheres are well correlated with major Precambrian crustal domains. The largest lithosphere thickness contrast coincides with the Snowbird Tectonic Zone, where the Hearne province extends down to 300 km, nearly 100 km deeper than the Proterozoic terranes in northern Alberta. In the latter region, a pronounced cylindrical negative velocity anomaly extends subvertically from 75 to 300‐km depth, which potentially results from significant tectonothermal modifications during subduction and/or plume activities. At the basin scale, mantle velocities show no apparent correlations with surface heat flux, suggesting a minimum mantle contribution to the regional thermal variability. Furthermore, the long‐wavelength isostatic gravity correlates negatively with the velocities, which confirms that the melt extraction from Precambrian cratons is responsible for the formation of highly depleted mantle lithospheres. Moreover, our model reveals the increased concentrations of kimberlites and lamproites near the zones of high horizontal velocity gradients. The distinct spatial pattern may reflect either preferential formation or eruption of potentially diamondiferous rocks at lithospheric weak zones near the western margin of Laurentia. Key Points: High‐resolution P and S velocity models reveal a sharp Cordillera‐Craton boundary and well‐correlated mantle anomalies and crustal domains Correlation analysis of mantle velocity with heat flow and gravity data suggests melt depletion and enrichment in lithosphere of western Laurentia Kimberlites/lamproites preferentially occurred near the high‐velocity gradients marking potential weak zones in continental lithosphere